2017
DOI: 10.1021/acs.jmedchem.7b01066
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Selective Adenine-Based Scaffolds for Inactivation of Bacterial Histidine Kinases

Abstract: Bacterial histidine kinases (HKs) are quintessential regulatory enzymes found ubiquitously in bacteria. Apart from their regulatory roles, they are also involved in the production of virulence factors and conferring resistance to various antibiotics in pathogenic microbes. We have previously reported compounds that inhibit multiple HKs by targeting the conserved catalytic and ATP-binding (CA) domain. Herein, we conduct a detailed structure–activity relationship assessment of adenine-based inhibitors using bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…1b ). 11 Consistent with this, we found that the positional isomer in which the –NH 2 and –CH 3 groups are switched shows minimal activity (comparison of Rilu-3 and 7 , IC 50 = 1.4 mM). The more potent lead from the HTS, Rilu-2 , contains two benzothiazole rings, likely promoting additional polar interactions within the active site.…”
Section: Resultssupporting
confidence: 83%
“…1b ). 11 Consistent with this, we found that the positional isomer in which the –NH 2 and –CH 3 groups are switched shows minimal activity (comparison of Rilu-3 and 7 , IC 50 = 1.4 mM). The more potent lead from the HTS, Rilu-2 , contains two benzothiazole rings, likely promoting additional polar interactions within the active site.…”
Section: Resultssupporting
confidence: 83%
“…5). 18,21 Asp 411 and Gly 415 participate in hydrogen bonding interactions to the nitrogen atoms in the bicyclic core in the same manner to that observed in the adenine core. In addition, the pyridine nitrogen is predicted to participate in a hydrogen bond with Asn 380, mimicking the same interaction we had previously reported, though this may be water-mediated given the distance (3.3 Å).…”
mentioning
confidence: 70%
“…9 Initial attempts in the 1990s to identify bioactive molecules that targeted HKs were thwarted by problematic compounds that inhibited through aggregation of the protein. 16 Although research has been progressing to identify molecules that inhibit HKs, 1721 none have progressed to a clinical stage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the peptide approach, altering the peptide scaffold to construct pharmacologically enhanced peptidomimetic scaffolds could offer a viable pathway to make these lead compounds more druggable. Alternatively, diverging completely from the peptidic scaffolds into small molecule-based scaffolds that still interact with the target histidine kinase receptor, as was successfully implemented in several other systems, [90][91][92][93] may prove to be the way to convert these anti-virulence compounds into drug leads.…”
Section: Discussionmentioning
confidence: 99%